Surface modification of reduced graphene oxide film by Ti ion implantation technique for high dye-sensitized solar cells performance - Low, F.W.; Lai, Chin Wei; Hamid, Sharifah Bee Abd (Elsevier, 2017)
Titanium (Ti) ion implantation approach was used in the present study to modify the reduced graphene oxide nanosheet (rGO NS) by incorporating the Ti4+ ion (at various applied powers ranging from 50 to 250 W) onto the rGO NS to prepare photoanodes for Dye-Sensitized Solar Cell (DSSC). The surface morphologies, functional groups, optical properties and surface chemical states of the modified rGO based photoanode (rGO-TiO2 nanocomposite (NC)) were studied. Fourier transform infrared (FTIR) spectra coupled with the elemental/chemical states in X-ray photoelectron spectroscopy (XPS) analysis revealed the presence of Ti–O–C functional groups after the modification process. Besides, the average size of Ti ion was found to be 70–80 nm as incorporated with rGO NS. The spacing of anatase TiO2 onto rGO NS were reported as 0.35 nm and 0.34 nm under HRTEM analysis, respectively. Experimental result implied that 150 W was the optimum applied power for the surface modification to take place ascribed to the lowest possibility for the recombination to occur and the smallest energy band gap. On top of that, at 150 W, the electron transfer rate was also found to be the highest due to the highest availability of the carbon-atom vacancy holes for Ti4+ replacement. It was also discovered that the optimized power conversion efficiency (PCE) of 8.51% could be achieved in DSSC by implanting the Ti ion onto rGO NS-based photoanode using 150 W. Further increase of the applied power to 200 W or 250 W led to the undesirable recombination of the Ti ions and rGO NS due to the exceptional photocatalytic activity among N719 dye/rGO/TiO2 interfaces which interfered the charge transportation at the KI electrolyte/N719 dye/rGO/TiO2 interfaces.